Poetics of the Medial State of Emily Dickinson’s Persona - Wang, Yinping (Journal of Literary Studies)
Emily Dickinson, the famous 19th-century American poet with a passion for books, botany, and gardens, spent most of her life secluded in her bedroom, where she wrote some 1,800 poems, published only posthumously. Within four walls, the poet built an imaginary bridge between the real and the unreal. One of the most important characteristics relating to the poet is the unwitting creation of an immanent authorial mythology. This article is an analysis-reflection on the poet’s work, her artistic expression, and autofiction. The aim is to highlight the concept of boundary and medial state of the lyrical persona. A linguistic analysis of lexical and semantic syntagms of the poet’s works is carried out. The conceptual images of poetics, conveying the receptive potential of the poet’s worldview, are determined. Consideration of the use of stylistic forms of the poetic narrative was revealed as a priority for media-oriented analysis.